2021
DOI: 10.1017/s002202992100008x
|View full text |Cite
|
Sign up to set email alerts
|

Yield gap in milk production is considerable in Indian Himalayan state of Meghalaya

Abstract: Yield gaps in milk production are here defined as the differentials between the actual yield obtained by the dairy farmer and the potential farm yield (production achieved by the top 10% of farmers: Gap 2) as well as the differential between this potential farm yield and the yield registered in the research stations (Gap 1). Assessment of yield gaps provides valuable information on potential production enhancement and drivers behind yield gaps. Milk production can be increased by narrowing the predominant larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(17 reference statements)
1
2
0
Order By: Relevance
“…In WKH, actual farm yield was observed to be 0.79 L/day to make the YG-2 of 27.85% whereas, in SWKH, the actual farm yield was 0.99 L/day raising the YG-2 to 37.37%. These results were in conformity with Kemboi et al 2021 in which they found total yield gap (91.06%) per day, composed of (11.76%) per day of yield gap-1 and (79.30%) per day of yield gap-2 and further explained that the top performing farms were achieving a production level not dissimilar to that obtained on the research stations, but many were doing far less well. After computing and summing up these, the total yield gap turned out to be 244.83% in the state of Meghalaya while it was 279.75% and 203.03% in districts of WKH and SWKH, respectively.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In WKH, actual farm yield was observed to be 0.79 L/day to make the YG-2 of 27.85% whereas, in SWKH, the actual farm yield was 0.99 L/day raising the YG-2 to 37.37%. These results were in conformity with Kemboi et al 2021 in which they found total yield gap (91.06%) per day, composed of (11.76%) per day of yield gap-1 and (79.30%) per day of yield gap-2 and further explained that the top performing farms were achieving a production level not dissimilar to that obtained on the research stations, but many were doing far less well. After computing and summing up these, the total yield gap turned out to be 244.83% in the state of Meghalaya while it was 279.75% and 203.03% in districts of WKH and SWKH, respectively.…”
Section: Resultssupporting
confidence: 89%
“…In case of pregnant heifer, standard animal unit was observed only in WKH, although it was very low (0.04 SAU). Contrary to it, similar study of Kemboi et al 2021 in Meghalaya indicated that the average number of cattle per household was 9.38 in standard animal units.…”
Section: Resultsmentioning
confidence: 84%
“…The scant literature on the dairy yield gap tends to examine mixed crop and livestock farmers in Sub-Saharan Africa (Henderson, et al 2016), cross-bred cattle in the North-Eastern state of India (Paul and Chandel, 2010), milk production in the Indian Himalayan state of Meghalaya (Kemboi, et al 2021), attainable bovine milk yields in Ethiopia and India (Mayberry, et al 2017) and genetic yield potential of milk in Pakistan (Iqbal & Ahmad, 1999).…”
Section: Introductionmentioning
confidence: 99%